It Takes a Motive: Communal and Agentic Articulated Interest and Candidate Emergence. (December 2020) - Conroy, Meredith; Green, Jon
More women ran for office in 2018 than any previous election year. This represents progress toward parity, but it remains unclear whether this surge in women's political ambition signals an easing of the candidate emergence path, which has typically favored men. We leverage over ten thousand intake forms of prospective candidates provided by Run for Something, a candidate recruitment nonprofit founded in 2017, to examine patterns in candidate emergence based on articulated interest through the lens of "communion" and "agency, " two basic behavioral orientations with gendered significance. We find that differences in articulated interest along the dimensions of communion and agency are greater between candidates and noncandidates than they are between men and women, supporting previous findings of similarities in men and women who emerge as candidates. Our results suggest the candidate emergence path is still easier for women (and men) whose motives are congruent with agency, and therefore the "masculine ethos" of politics.